Light conversion anti-subfissure film as well as preparation method and application thereof

By using a light-conversion anti-hidden crack film containing a light conversion coating of rare earth nanomaterials in flexible photovoltaic modules, the poor weather resistance and hidden cracking problems of flexible materials under ultraviolet irradiation are solved, and efficient photoelectric conversion and anti-hidden cracking effects are achieved.

CN119531147APending Publication Date: 2025-02-28ZHONGCHUANG KEDA (FOSHAN) TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411741090.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The flexible materials in existing flexible photovoltaic modules have poor toxicity and weather resistance. They are prone to changes and easily produce hidden cracks under ultraviolet irradiation for a long time, resulting in low power generation efficiency.

Method used

A light conversion anti-crack film is adopted, which includes a substrate layer and a light conversion coating arranged on the surface of the substrate layer. The light conversion coating is made of a mixture of epoxy resin and a light conversion material. The light conversion material includes a rare earth nanomaterial, and the rare earth nanomaterial includes a ultraviolet light-to-visible rare earth nanomaterial.

Benefits of technology

By mixing rare earth nanomaterials with epoxy resin, the light conversion coating can absorb ultraviolet light from sunlight and convert it into visible light, preventing the substrate layer from yellowing, improving power generation efficiency, extending service life, and achieving anti-hidden cracking effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119531147A_ABST
    Figure CN119531147A_ABST
Patent Text Reader

Abstract

The invention discloses a light conversion anti-subfissure film and a preparation method and application thereof.The light conversion anti-subfissure film comprises a base material layer and a light conversion coating arranged on the surface of the base material layer, the light conversion coating is prepared by mixing epoxy resin and a light conversion material, and the light conversion material comprises an ultraviolet light-to-visible light rare earth nano material. According to the light conversion subfissure prevention film, the ultraviolet light-to-visible light rare earth nano material is added into the light conversion coating, so that ultraviolet light in sunlight can be absorbed and converted into available visible light, the problem that the base material layer is yellowed under long-term irradiation of the ultraviolet light is prevented, and compared with the traditional technology that an ultraviolet conversion layer needs to be independently arranged, the light conversion subfissure prevention film has the advantages that the cost is reduced; the light conversion coating is prepared by mixing the rare earth nano material and the epoxy resin, and the obtained light conversion coating is good in permeability, has excellent mechanical strength, can effectively resist bending, realizes an anti-subfissure effect, delays aging of the flexible photovoltaic module, improves the luminous efficiency of the flexible photovoltaic module, and prolongs the service life of the flexible photovoltaic module.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible photovoltaic devices, and relates to a light conversion film and a preparation method and application thereof, and specifically relates to a light conversion anti-hidden crack film and a preparation method and application thereof. Background Art

[0002] With the gradual reduction of exploitable natural resources such as oil and natural gas, the development and utilization of clean energy has received more extensive attention. Among them, solar power generation technology has developed rapidly due to its advantages such as abundant resources, long life, wide distribution, safety, cleanliness, reliable technology, and can be converted into a variety of other forms of energy.

[0003] Solar photovoltaic power generation refers to a power generation method that directly converts light energy into electrical energy without going through a thermal process. It includes photovoltaic power generation, photochemical power generation, photoinduction power generation and photobiological power generation. Photovoltaic power generation is a direct power generation method that uses semiconductor electronic devices to effectively absorb solar radiation energy and convert it into electrical energy. This technology is mature, low-cost and widely used, and is the mainstream of solar power generation today. Traditional photovoltaic modules generally use rigid materials such as glass, aluminum and silicon, and photovoltaic modules are generally heavy. Because they cannot be bent, they cannot be used in various scenarios such as color steel tile roofs, flat roofs, and residential tile houses. At the same time, the bearing capacity of various types of roofs is different, and traditional photovoltaic modules are at a disadvantage, which hinders their application in the field of distributed photovoltaics. In order to solve the above problems, in recent years, the industry has developed flexible photovoltaic module technology. Flexible photovoltaic modules are glass-free encapsulation of modules through high molecular polymer materials. They are replacing traditional rigid photovoltaic modules with their thin, flexible characteristics and high energy conversion rate. Flexible photovoltaic modules can adapt to curved, bent or irregular surfaces, can be combined with various scenarios for application, and can be widely used in various fields.

[0004] Flexible photovoltaic modules are generally composed of a front panel, a film, a solar cell and a back panel. The back panel material of a flexible photovoltaic module is usually a flexible polymer film, and the front panel material of a flexible photovoltaic module is mostly glass fiber cloth. The selection of these materials can greatly reduce the weight of the photovoltaic module. Most of the existing flexible photovoltaic modules use a composite of resin and glass fiber cloth as the front panel material. During the use of flexible photovoltaic modules, ultraviolet rays have a damaging effect on photovoltaic cells, which will accelerate the aging of solar cells and reduce their conversion efficiency. At the same time, for conventional flexible photovoltaic modules that use a combination of glass fiber and polymer resin as a flexible panel, the performance of the polymer resin will also change under long-term ultraviolet irradiation, and the glass fiber cloth has a weak resistance to environmental aging and is prone to yellowing during use, which will reduce the power generation efficiency of subsequent modules. To solve this technical problem, Chinese patent CN118221667A discloses an organic blue fluorescent material containing a benzothiazole structure, which can absorb ultraviolet light and release visible light, protect solar cells, and thus improve conversion efficiency; Chinese patent CN220420593U discloses a color front panel, the color layer uses a quantum dot coating layer, the color layer converts ultraviolet light into visible light, improves the visible light transmittance of the photovoltaic front panel, and improves the utilization rate of photovoltaic modules. However, the above technology has the following technical problems: organic fluorescent materials have the problems of toxicity and poor weather resistance, and the existing resin materials have complex components, are prone to change, and have reduced permeability. At the same time, the flexible materials in the existing flexible photovoltaic modules are prone to small cracks, i.e., hidden cracks, under long-term use, resulting in reduced power generation efficiency of the photovoltaic modules.

[0005] In view of this, the flexible materials in the flexible photovoltaic modules in the prior art are further improved. Summary of the invention

[0006] To this end, the technical problem to be solved by the present invention is that the flexible materials in the existing flexible photovoltaic modules are toxic and have poor weather resistance, and are prone to changes and hidden cracks under long-term ultraviolet irradiation, resulting in low power generation efficiency. Therefore, a non-toxic, weather-resistant, and high-power generation efficiency light conversion anti-hidden crack film and its preparation method and application are proposed.

[0007] In order to solve the above technical problems, the technical solution of the present invention is:

[0008] A first aspect of the present invention provides a light-conversion anti-crack film, which includes a substrate layer and a light-conversion coating arranged on the surface of the substrate layer, the light-conversion coating is made by mixing epoxy resin and light-conversion material, the light-conversion material includes rare earth nanomaterials, and the rare earth nanomaterials include ultraviolet light-visible light rare earth nanomaterials.

[0009] Preferably, the rare earth nanomaterial also includes infrared light-to-visible light rare earth nanomaterial.

[0010] Preferably, the epoxy resin is a nano-silicon dioxide-modified alicyclic epoxy resin, in which the amount of nano-silicon dioxide added is 10%-30% of the alicyclic epoxy resin, the viscosity of the nano-silicon dioxide-modified alicyclic epoxy resin is 600Pas-5000Pas, and the solid content of the sol is 30%-50%.

[0011] Preferably, the rare earth nanomaterial is selected from Y 2 O 3 :Eu 3+ , Y 2 O 3 :Tb 3+ , Y 2 O 2 S:Tb 3+ ,Dy 3+ 、YAG:Tb 3+ , Gd 2 O 2 S:Tb 3+ 、SrAl 2 O 4 :Eu 2+ ,Dy 3+ , CaAl 2 O 4 :Eu 2+ ,Dy 3+ ,LiGdF 4 :Eu 3+ 、YPO 4 :Yb 3+ ,Tm 3+ ,LiGdF 4 :Eu 3 + 、KCaGd(PO 4 ) 2 :Eu 3+ 、YAB:Cr 3+ ,Yb 3+ 、YVO 3 :Yb 3+ , Y 2 O 3 :Bi 3+ ,Yb 3+ 、YAG:Ce 3+ ,Cr 3+ ,Yb 3+ , Gd 2 O 3 :Yb 3 + ,Er 3+ ,NaYF 4 :Yb 3+ ,Er3+ At least one of .

[0012] Preferably, the photoconversion material is a photoconversion material dispersion, and in the photoconversion coating, the added amount of the photoconversion dispersion is 1%-30% of the epoxy resin; the photoconversion material dispersion includes the following components in mass percentage: 10%-30% rare earth nanomaterial, 5%-15% dispersant, and 65%-80% solvent.

[0013] Preferably, the dispersant is at least one of BYK-163, BYK-110, DiSpers-685, BYK-104, EFKA-4010, EFKA-5220, S-32500, S-20000, EFKA-4330, EFKA-4310, and BYK-104S; and the solvent is at least one of dibutyl phthalate, ethyl acetate, acetone, ethanol, cyclohexanone, and toluene.

[0014] Preferably, the substrate layer is a glass fiber composite material layer, and the gram weight of the substrate layer is 40-150g / m 2 .

[0015] The second aspect of the present invention provides a method for preparing the light conversion anti-crack film, which comprises the following steps:

[0016] dispersing the light conversion material in the epoxy resin to obtain a composite epoxy resin;

[0017] The composite epoxy resin is coated on the substrate layer and cured to form a light conversion coating to obtain the light conversion film.

[0018] Preferably, the curing temperature is 120° C.-150° C., and the curing time is 1-3 hours.

[0019] A third aspect of the present invention provides an application of the light conversion anti-crack film in a flexible photovoltaic module.

[0020] The above technical solution of the present invention has the following advantages compared with the prior art:

[0021] (1) The light conversion anti-hidden crack film provided by the present application includes a substrate layer and a light conversion coating disposed on the surface of the substrate layer. The light conversion coating is prepared by mixing epoxy resin and light conversion material. The light conversion material includes rare earth nanomaterials, and the rare earth nanomaterials include ultraviolet light-visible light rare earth nanomaterials. The light conversion anti-hidden crack film copper adds ultraviolet light-visible light rare earth nanomaterials to the light conversion coating, which can absorb ultraviolet light in sunlight and convert it into usable visible light, thereby preventing the substrate layer from yellowing under long-term ultraviolet light irradiation. Compared with the traditional technology that requires a separate ultraviolet conversion layer, the present application prepares the light conversion coating by mixing rare earth nanomaterials with epoxy resin. The nano-silicon dioxide modified epoxy resin sol is transparent and has excellent mechanical strength and can effectively resist bending, thereby making the obtained light conversion coating have good permeability and mechanical strength, achieving the effect of preventing hidden cracks, delaying the aging of flexible photovoltaic modules, and improving the luminous efficiency and service life of flexible photovoltaic modules.

[0022] (2) The light-conversion anti-crack film provided in the present application, the rare earth nanomaterial also includes infrared light-to-visible light rare earth nanomaterials. The light-conversion anti-crack film can also absorb infrared rays that cannot be used in solar energy and convert infrared light into usable visible light, further improving the power generation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein

[0024] Figure 1 is an emission spectrum diagram of the light conversion anti-crack film provided by Example 4 of the present invention;

[0025] Figure 2 is an emission spectrum diagram of the light conversion anti-crack film provided in Example 5 of the present invention;

[0026] Figure 3 This is a white and opaque film obtained after adding silica gel and curing in Comparative Example 5;

[0027] Figure 4 The film obtained after adding polyurethane and curing in Comparative Example 6 is partially white and has bubbles. DETAILED DESCRIPTION

[0028] Example 1

[0029] The present embodiment provides a light conversion anti-hidden crack film, which includes a substrate layer of glass fiber composite material and a light conversion coating coated on the surface of the substrate layer. The light conversion coating is prepared by mixing epoxy resin and light conversion material, the light conversion material includes rare earth nanomaterials, the rare earth nanomaterials include ultraviolet light to visible light rare earth nanomaterials, and in this embodiment, preferably, the rare earth nanomaterials also include infrared light to visible light rare earth nanomaterials. Among them, the epoxy resin is a nano-silicon dioxide modified alicyclic epoxy resin, the epoxy resin is a nano-silicon dioxide modified alicyclic epoxy resin, which is transparent, has a viscosity of 600Pas, and a sol solid content of 30%. In the nano-silicon dioxide modified alicyclic epoxy resin, the amount of nano-silicon dioxide added is 10% of the alicyclic epoxy resin. The light conversion material is in the form of a light conversion material dispersion liquid. In the light conversion coating, the amount of light conversion dispersion liquid added is 1% of the epoxy resin. The light conversion material dispersion liquid is composed of the following components by mass percentage: 10% of rare earth nanomaterials, 15% of dispersant, and 75% of solvent. In this embodiment, the rare earth nanomaterial is Y 2 O 3 :Tb 3+ The dispersant is BYK-163, the solvent is acetone, and the glass fiber composite material can be glass fiber cloth with a gram weight of 40g / m 2 .

[0030] This embodiment also provides a method for preparing the above-mentioned light conversion anti-crack film, comprising the following steps:

[0031] S1. Evenly mix the rare earth nanomaterial, the dispersant and the solvent, and grind them in a sand mill for 10 hours to obtain a light conversion material dispersion.

[0032] S2. Dispersing the light conversion material dispersion in the epoxy resin to obtain a composite epoxy resin.

[0033] S3, coating the composite epoxy resin on the surface of the glass fiber cloth, and curing it at 120° C. for 1 hour to form a light conversion coating, so that the light conversion coating and the glass fiber cloth are combined to obtain a light conversion anti-hidden crack film.

[0034] The present embodiment also provides an application of the above-mentioned light-conversion anti-hidden crack film in a flexible photovoltaic module. The flexible photovoltaic module is formed by laminating PET, EVA film, CPC, composite film, battery cell, composite film, CPC, EVA film, and ETFE in sequence, wherein the composite film is the light-conversion anti-hidden crack film provided in the present embodiment.

[0035] The light conversion anti-hidden crack film provided in this embodiment is prepared by mixing rare earth nanomaterials with epoxy resin, and then stacking and curing with the substrate layer. The rare earth nanomaterials can absorb ultraviolet light in sunlight to avoid the problem of yellowing of the substrate layer of the glass fiber composite material under long-term exposure to ultraviolet light. At the same time, the light conversion material can convert ultraviolet light into usable visible light, thereby improving the power generation efficiency of the final flexible photovoltaic module product. The nano-silicon dioxide-modified epoxy resin material has high transparency, strong weather resistance, excellent mechanical strength, and can effectively resist bending, thereby making the obtained light conversion coating have good permeability and mechanical strength, achieving the effect of anti-hidden cracking, delaying the aging of the flexible photovoltaic module, and improving the luminous efficiency and service life of the flexible photovoltaic module. The light conversion anti-hidden crack film can also absorb infrared light that cannot be used in solar energy, and convert infrared light into usable visible light, further improving the power generation efficiency.

[0036] Example 2

[0037] The present embodiment provides a light-conversion anti-hidden crack film, which includes a substrate layer of glass fiber composite material and a light-conversion coating coated on the surface of the substrate layer. The light-conversion coating is prepared by mixing epoxy resin and light-conversion material, the light-conversion material includes rare earth nanomaterials, the rare earth nanomaterials include ultraviolet light-visible light rare earth nanomaterials, and in this embodiment, preferably, the rare earth nanomaterials also include infrared light-visible light rare earth nanomaterials. Among them, the epoxy resin is a nano-silicon dioxide-modified alicyclic epoxy resin, the epoxy resin is a nano-silicon dioxide-modified alicyclic epoxy resin, it is transparent, its viscosity is 5000Pas, the sol solid content is 50%, and in the nano-silicon dioxide-modified alicyclic epoxy resin, the amount of nano-silicon dioxide added is 30% of the alicyclic epoxy resin. The photoconversion material is in the form of a photoconversion material dispersion. In the photoconversion coating, the amount of the photoconversion dispersion added is 30% of the epoxy resin. The photoconversion material dispersion is composed of the following components by mass percentage: 30% of rare earth nanomaterial, 5% of dispersant, and 65% of solvent. In this embodiment, the rare earth nanomaterial is LiGdF 4 :Eu 3+ The dispersant is EFKA-4010, the solvent is ethanol, and the glass fiber composite material can be glass fiber cloth with a gram weight of 150g / m 2 .

[0038] This embodiment also provides a method for preparing the above-mentioned light conversion anti-crack film, comprising the following steps:

[0039] S1. Evenly mix the rare earth nanomaterial, the dispersant and the solvent, and grind them in a sand mill for 20 hours to obtain a light conversion material dispersion.

[0040] S2. Dispersing the light conversion material dispersion in the epoxy resin to obtain a composite epoxy resin.

[0041] S3, coating the composite epoxy resin on the surface of the glass fiber cloth, and curing it at 150° C. for 3 hours to form a light conversion coating, so that the light conversion coating and the glass fiber cloth are combined to obtain a light conversion anti-hidden crack film.

[0042] Example 3

[0043] The present embodiment provides a light-conversion anti-hidden crack film, which includes a substrate layer of glass fiber composite material and a light-conversion coating coated on the surface of the substrate layer. The light-conversion coating is prepared by mixing epoxy resin and light-conversion material, the light-conversion material includes rare earth nanomaterials, the rare earth nanomaterials include ultraviolet light-visible light rare earth nanomaterials, and in this embodiment, preferably, the rare earth nanomaterials also include infrared light-visible light rare earth nanomaterials. Among them, the epoxy resin is a nano-silicon dioxide-modified alicyclic epoxy resin, the epoxy resin is a nano-silicon dioxide-modified alicyclic epoxy resin, it is transparent, its viscosity is 1500Pas, the sol solid content is 40%, and in the nano-silicon dioxide-modified alicyclic epoxy resin, the amount of nano-silicon dioxide added is 20% of the alicyclic epoxy resin. The photoconversion material is in the form of a photoconversion material dispersion. In the photoconversion coating, the amount of the photoconversion dispersion added is 15% of the epoxy resin. The photoconversion material dispersion is composed of the following components by mass percentage: 20% of rare earth nanomaterial, 10% of dispersant, and 70% of solvent. In this embodiment, the rare earth nanomaterial is Y 2 O 3 :Bi 3+ ,Yb 3+ The dispersant is BYK-104S, the solvent is toluene, and the glass fiber composite material can be glass fiber cloth with a gram weight of 80g / m 2 .

[0044] This embodiment also provides a method for preparing the above-mentioned light conversion anti-crack film, comprising the following steps:

[0045] S1. Evenly mix the rare earth nanomaterial, the dispersant and the solvent, and grind them in a sand mill for 16 hours to obtain a light conversion material dispersion.

[0046] S2. Dispersing the light conversion material dispersion in the epoxy resin to obtain a composite epoxy resin.

[0047] S3, coating the composite epoxy resin on the surface of the glass fiber cloth, and curing it at 140° C. for 2 hours to form a light conversion coating, so that the light conversion coating and the glass fiber cloth are combined to obtain a light conversion anti-hidden crack film.

[0048] Example 4

[0049] This embodiment provides a light conversion anti-crack film, which is prepared by the following method:

[0050] 50g of Y2 O 3 :Eu 3+ The rare earth nanomaterial was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod nitrate sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, add the purchased nano-silicon dioxide modified epoxy resin sol to the alicyclic epoxy resin to obtain a composite epoxy resin, the resin sol viscosity is 650Pas, the amount of nano-silicon dioxide added is 20% of the alicyclic resin, and the solid content of the resin sol is 40%. Then add the light conversion dispersion to the composite epoxy resin, mix evenly, apply it on the glass fiber cloth and solidify to obtain a light conversion film. The amount of light conversion dispersion added to the composite epoxy resin is 2%, and the weight of the glass fiber cloth is 100g / m 2 .

[0051] Example 5

[0052] This embodiment provides a light conversion anti-crack film, which is prepared by the following method:

[0053] 45g of Gd 2 O 3 :Yb 3+ ,Er 3+ The rare earth nanomaterial was added to 180 g of ethyl acetate, 27 g of dispersant DiSpers-685 was added, and the mixture was sand-milled for 20 h in a rod nitrate sand mill with 0.1-0.3 mm Yb-stabilized zirconium oxide beads to obtain Gd 2 O 3 :Yb 3+ ,Er 3+ Light conversion dispersion, add the purchased nano-silicon dioxide modified epoxy resin sol to the alicyclic epoxy resin to obtain a composite epoxy resin, the resin sol viscosity is 4500Pas, the amount of nano-silicon dioxide added is 20% of the alicyclic resin, and the solid content of the resin sol is 45%. Then add the light conversion dispersion to the composite epoxy resin, mix evenly, apply it on the glass fiber cloth and solidify to obtain a light conversion anti-hidden crack film. The amount of light conversion dispersion added to the composite epoxy resin is 3%, and the weight of the glass fiber cloth is 150g / m 2 .

[0054] Comparative Example 1

[0055] This comparative example provides a light conversion anti-crack film, and the preparation method thereof is as follows:

[0056] 50g of Y 2 O 3 :Eu 3+The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, add the purchased nano-silicon dioxide modified epoxy resin sol to the alicyclic epoxy resin to obtain a composite epoxy resin, the resin sol viscosity is 650Pas, the amount of nano-silicon dioxide added is 20% of the alicyclic resin, and the solid content of the resin sol is 40%. Then add the light conversion dispersion to the composite epoxy resin, mix evenly, apply it on the glass fiber cloth and solidify it to obtain a light conversion anti-hidden crack film. The amount of light conversion dispersion added to the composite epoxy resin is 11%, and the weight of the glass fiber cloth is 100g / m 2 , the amount of the dispersion added was changed to 11% relative to Example 4.

[0057] Comparative Example 2

[0058] This comparative example provides a light conversion anti-crack film, and the preparation method thereof is as follows:

[0059] 50g of Y 2 O 3 :Eu 3+ The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, add the purchased nano-silicon dioxide modified epoxy resin sol to the alicyclic epoxy resin to obtain a composite epoxy resin, the resin sol viscosity is 4500Pas, the amount of nano-silicon dioxide added is 20% of the alicyclic resin, and the solid content of the resin sol is 45%. Then add the light conversion dispersion to the composite epoxy resin, mix evenly, apply it on the glass fiber cloth and solidify it to obtain a light conversion anti-hidden crack film. The amount of light conversion dispersion added to the composite epoxy resin is 3%, and the gram weight of the glass fiber cloth is 200g / m 2 Compared with Example 4, only the weight of the glass fiber cloth is changed to 200g / m 2 .

[0060] Comparative Example 3

[0061] This comparative example provides a light conversion anti-crack film, and the preparation method thereof is as follows:

[0062] 50g of Y 2 O 3 :Eu 3+The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, add the purchased nano-silicon dioxide modified epoxy resin sol to the alicyclic epoxy resin to obtain a composite epoxy resin, the resin sol viscosity is 650Pas, the addition amount is 20% of the alicyclic resin, and the solid content of the resin sol is 40%. Then add the light conversion dispersion to the composite epoxy resin, mix evenly, apply it on the glass fiber cloth and solidify to obtain a light conversion anti-hidden crack film. The addition amount of light conversion dispersion in the composite epoxy resin is 0.5%, and the gram weight of the glass fiber cloth is 100g / m 2 Compared with Example 4, only the amount of the dispersion added was changed to 0.5%.

[0063] Comparative Example 4

[0064] This comparative example provides a light conversion anti-crack film, and the preparation method thereof is as follows:

[0065] The purchased nano-silicon dioxide modified epoxy resin sol was added to the alicyclic epoxy resin to obtain a composite epoxy resin. The viscosity of the resin sol was 650Pas, the addition amount was 20% of the alicyclic resin, and the solid content of the resin sol was 40%. The composite epoxy resin was then directly mixed and evenly coated on the glass fiber cloth and cured to obtain a light conversion anti-hidden crack film. The weight of the glass fiber cloth was 100g / m 2 Compared with Example 4, the only difference is that the light conversion material is not added.

[0066] Comparative Example 5

[0067] This comparative example provides a light conversion anti-crack film, and the preparation method thereof is as follows:

[0068] 50g of Y 2 O 3 :Eu 3+ The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, light conversion material dispersion is added to silica gel, glass fiber cloth is laid on the battery sheet, and finally composite silica gel is coated on the glass fiber cloth and cured to obtain light conversion anti-hidden crack film. The amount of light conversion dispersion added to silica gel is 2%, and the weight of glass fiber cloth is 100g / m 2 , compared with Example 4, only the composite epoxy resin is replaced by silica gel.

[0069] Comparative Example 6

[0070] This comparative example provides a light conversion anti-crack film, and the preparation method thereof is as follows:

[0071] 50g of Y 2 O 3 :Eu 3+ The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, light conversion material dispersion is added to polyurethane resin, glass fiber cloth is laid on the battery sheet, and finally the composite resin is coated on the glass fiber cloth and cured to obtain a light conversion anti-hidden crack film. The amount of light conversion dispersion added to the epoxy resin is 2%, and the weight of the glass fiber cloth is 100g / m 2 , compared with Example 4, only the composite epoxy resin is replaced by polyurethane resin.

[0072] Comparative Example 7

[0073] This comparative example provides a light conversion film, and the preparation method thereof is as follows:

[0074] 50g of Y 2 O 3 :Eu 3+ The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, light conversion material dispersion is added to acrylic resin, glass fiber cloth is laid on the battery sheet, and finally acrylic resin is coated on the glass fiber cloth and cured to obtain light conversion anti-hidden crack film. The amount of light conversion dispersion added to acrylic resin is 2%, and the weight of glass fiber cloth is 100g / m 2 , compared with Example 4, only the composite epoxy resin is replaced by acrylic resin.

[0075] Comparative Example 8

[0076] This comparative example provides a light conversion film, and the preparation method thereof is as follows:

[0077] 50g of Y 2 O 3 :Eu 3+The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, light conversion material dispersion is added to bisphenol A epoxy resin, glass fiber cloth is laid on the battery cell, and finally the composite epoxy resin is cured on the glass fiber cloth to obtain a light conversion anti-hidden crack film. The amount of light conversion dispersion added to the epoxy resin is 2%, and the weight of the glass fiber cloth is 100g / m 2 , compared with Example 4, only the composite epoxy resin is replaced with bisphenol A type epoxy resin.

[0078] Comparative Example 9

[0079] This comparative example provides a light conversion film, and the preparation method thereof is as follows:

[0080] A glass fiber cloth is laid on the cell sheet, and then bisphenol A epoxy resin is directly coated on the glass fiber cloth and cured to obtain a film. 2 O 3 :Eu 3+ .

[0081] Comparative Example 10

[0082] This comparative example provides a light conversion film, and the preparation method thereof is as follows:

[0083] 50g of Y 2 O 3 :Eu 3+ The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, light conversion material dispersion is added to alicyclic epoxy resin, glass fiber cloth is laid on the battery cell, and finally the composite epoxy resin is cured on the glass fiber cloth to obtain a light conversion anti-hidden crack film. The amount of light conversion dispersion added to the epoxy resin is 2%, and the weight of the glass fiber cloth is 100g / m 2 , relative to Example 1, only the composite epoxy resin is replaced with the same alicyclic epoxy resin as in Example 4.

[0084] Comparative Example 11

[0085] This comparative example provides a light conversion film, and the preparation method thereof is as follows:

[0086] 50g of Y2 O 3 :Eu 3+ The light conversion material was added to 116 g of dibutyl phthalate, and then 16 g of dispersant EFKA-5220 was added, and Yb was obtained by sand milling with 0.1-0.3 mm Yb-stabilized zirconium oxide beads in a rod niter sand mill for 15 h. 2 O 3 :Eu 3+ Light conversion dispersion, light conversion material dispersion is added to alicyclic epoxy resin, and then the purchased nano-silicon dioxide dispersion is added to the above alicyclic epoxy resin. The silicon dioxide content in the dispersion is the same as the effective silicon dioxide content in the modified resin of Example 1. Glass fiber cloth is laid on the battery cell, and finally the composite epoxy resin is cured on the glass fiber cloth to obtain a light conversion anti-hidden crack film. The amount of light conversion dispersion added to the epoxy resin is 2%, and the weight of the glass fiber cloth is 100g / m 2 Compared with Example 4, only the composite epoxy resin is replaced with an alicyclic epoxy resin added with a nano-silicon dioxide dispersion.

[0087] Experimental example

[0088] 1. The light conversion anti-hidden crack films in Examples 4-5 and Comparative Examples 1-4 were prepared into flexible photovoltaic modules: PET, EVA film, CPC, anti-hidden crack film, battery sheet, anti-hidden crack film, CPC, EVA film, and ETFE were laminated in this order. The photovoltaic module was tested for photoelectric conversion efficiency according to the method of GB / T 34160-2017, and the light conversion anti-hidden crack films in Examples 4-5 and Comparative Examples 1-4 were tested for light transmittance. The results are shown in Table 1 below:

[0089] Table 1

[0090]

[0091] The above test results show that the photoelectric conversion efficiency after adding the photoconversion material is higher than that without adding the photoconversion material. The amount of photoconversion material added will affect the light transmittance of the anti-crack film, and the photoelectric conversion efficiency will also be affected. At the same time, the thickness of the glass fiber cloth will also affect the light transmittance and photoelectric conversion efficiency. The photovoltaic panel prepared in the embodiment of the present application can effectively improve the photoelectric conversion efficiency.

[0092] 2. The anti-hidden crack films obtained in Example 4 and Comparative Examples 5-8, Comparative Example 10, and Comparative Example 11 were laminated in the order of PET, EVA film, CPC, anti-hidden crack film, battery sheet, anti-hidden crack film, CPC, EVA film, and ETFE to form solar photovoltaic modules. The curling performance of the above embodiments was tested according to the method in JGT535-2017. The results are shown in Table 2 below:

[0093] Table 2

[0094]

[0095]

[0096] The test results of the crack-proof films obtained from Example 4 and 6 comparative examples show that the strength of alicyclic and bisphenol A epoxy resins after curing is relatively high, and the strength of alicyclic resin is slightly higher than that of bisphenol A epoxy resin after curing. Current discontinuity only occurs during the wet leakage current test, indicating that there are cracks in the battery cell. The results of Example 4 and Comparative Example 11 show that the addition of nano-silicon dioxide dispersion will affect the transparency of the resin and make the epoxy resin more brittle and less resistant to bending. The results of Example 4 and Comparative Example 10 show that the addition of nano-silicon dioxide modified alicyclic epoxy resin is beneficial to increase the strength of alicyclic epoxy resin, so that it does not have short circuits and current discontinuity in the test, effectively preventing cracks that cannot be observed and identified by the naked eye. However, silicone, polyurethane, and acrylic resins have low strength and whitening after curing, which cannot meet the performance requirements of flexible photovoltaic modules for transparency and strength.

[0097] 3. The films made of Example 4, Comparative Example 8, Comparative Example 9, and Comparative Example 10 were subjected to accelerated aging tests according to the method of standard GB / T41203-2021. After the test, the yellowing index was tested. The results are shown in Table 3 below:

[0098] Table 3

[0099] Yellowing index ΔYi Example 4 0.9 Comparative Example 8 6 Comparative Example 9 15 Comparative Example 10 1

[0100] The above test results show that the yellowing index is significantly reduced after the addition of photoconversion materials. The test results of Comparative Examples 8 and 10 show that the anti-yellowing performance of bisphenol A resin is worse than that of alicyclic epoxy resin, and bisphenol A epoxy resin is not resistant to aging compared with alicyclic epoxy resin. Comparison between Comparative Example 8 and Comparative Example 9 shows that the anti-yellowing index is improved after the addition of photoconversion materials, and the addition of photoconversion materials enhances the anti-aging performance of the film layer.

[0101] 4. The emission spectrum of the light conversion anti-crack film provided in Example 4 is tested. The test results are as follows: Figure 1 As shown, specifically, Figure 1 The addition of Y provided in Example 4 2 O 3 :Eu 3+ Emission spectrum of the light conversion anti-crack film obtained after converting the ultraviolet to visible light conversion material.

[0102] 5. The emission spectrum of the light conversion anti-crack film provided in Example 5 is tested. The test results are as follows: Figure 2 As shown. Figure 1 Example 5 provides the addition of Gd2 O 3 :Yb 3+ ,Er 3+ Emission spectrum of the light conversion crack film obtained after the infrared to visible light conversion material.

[0103] 6. Comparative Example 5 The appearance of the light conversion anti-crack film provided in Comparative Example 6 is as follows Figure 3-4 As shown in the figure, it can be seen that the film obtained after adding silicone and curing is whitish and opaque, and the film obtained after adding polyurethane resin and curing is partially whitish and has bubbles.

[0104] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A light conversion anti-crack film, characterized in that: It comprises a substrate layer and a light conversion coating arranged on the surface of the substrate layer. The light conversion coating is prepared by mixing epoxy resin and light conversion material. The light conversion material comprises rare earth nanomaterials, and the rare earth nanomaterials comprise ultraviolet light-visible light conversion rare earth nanomaterials.

2. The light conversion anti-crack film according to claim 1, characterized in that: The rare earth nanomaterials also include infrared light-to-visible light rare earth nanomaterials.

3. The light conversion anti-crack film according to claim 1 or 2, characterized in that: The epoxy resin is an alicyclic epoxy resin modified by nano-silicon dioxide. In the alicyclic epoxy resin modified by nano-silicon dioxide, the addition amount of nano-silicon dioxide is 10%-30% of the alicyclic epoxy resin. The viscosity of the alicyclic epoxy resin modified by nano-silicon dioxide is 600Pas-5000Pas, and the solid content of the sol is 30%-50%.

4. The light conversion anti-crack film according to claim 3, characterized in that: The rare earth nanomaterial is selected from Y2O3:Eu 3+ 、Y2O3:Tb 3+ 、Y2O2S:Tb 3+ ,Dy 3+ 、YAG:Tb 3+ 、Gd2O2S:Tb 3+ 、SrAl2O4:Eu 2+ ,Dy 3+ 、CaAl2O4:Eu 2+ ,Dy 3 + 、LiGdF4:Eu 3+ 、YPO4:Yb 3+ ,Tm 3+ 、LiGdF4:Eu 3+ 、KCaGd(PO4)2:Eu 3+ 、YAB:Cr 3+ ,Yb 3+ 、YVO3:Yb 3+ 、Y2O3:Bi 3+ ,Yb 3+ 、YAG:Ce 3+ ,Cr 3+ ,Yb 3+ 、Gd2O3:Yb 3+ ,Er 3+ 、NaYF4:Yb 3+ ,Er 3+ At least one of .

5. The light conversion anti-crack film according to claim 4, characterized in that: The photoconversion material is a photoconversion material dispersion. In the photoconversion coating, the addition amount of the photoconversion dispersion is 1%-30% of the epoxy resin. The photoconversion material dispersion includes the following components by mass percentage: 10%-30% of rare earth nanomaterial, 5%-15% of dispersant, and 65%-80% of solvent.

6. The light conversion anti-crack film according to claim 5, characterized in that: The dispersant is at least one of BYK-163, BYK-110, DiSpers-685, BYK-104, EFKA-4010, EFKA-5220, S-32500, S-20000, EFKA-4330, EFKA-4310, and BYK-104S; and the solvent is at least one of dibutyl phthalate, ethyl acetate, acetone, ethanol, cyclohexanone, and toluene.

7. The light conversion anti-crack film according to claim 6, characterized in that: The substrate layer is a glass fiber composite material layer, and the gram weight of the substrate layer is 40-150g / m 2 .

8. A method for preparing the light conversion anti-crack film according to any one of claims 1 to 7, characterized in that: The steps include: dispersing the light conversion material in the epoxy resin to obtain a composite epoxy resin; The composite epoxy resin is coated on the substrate layer and cured to form a light conversion coating to obtain the light conversion film.

9. The preparation method according to claim 8, characterized in that: The curing temperature is 120° C.-150° C., and the curing time is 1-3 hours.

10. Use of the light conversion anti-crack film according to any one of claims 1 to 7 in a flexible photovoltaic module.

Citation Information

Patent Citations

  • Organic blue fluorescent material containing benzothiazole structure and application of organic blue fluorescent material in preparation of photovoltaic adhesive film

    CN118221667A

  • Colorful flexible photovoltaic front plate and photovoltaic module

    CN220420593U